MOLECULAR DIAGNOSIS of LEISHMANIA AMAZONENSIS IN A CAPTIVE SPIDER MONKEY IN BAURU, São Paulo, BRAZIL - Felix de Lima, Valeria Marcal [UNESP]; Bodini Santiago, Maria Emilia [UNESP]; Sanches, Leticia da Cruz [UNESP]; de Lima, Beatriz Dolabela (Amer Assoc Zoo Veterinarians, 2012)
The municipality of Bauru, São Paulo, Brazil, is an area endemic for leishmaniasis. At the zoo, a spider monkey (Ateles paniscus) showed nonpathognomonic symptoms, such as weight loss and pale mucous membranes. Blood was collected from the jugular vein and investigated for the presence of Leishmania spp. DNA by polymerase chain reaction and restriction fragment length polymorphism. Parasite DNA was detected, and the pattern observed was identical to Leishmania amazonensis. This study presents molecular evidence of L. amazonensis infection in a captive spider monkey.
Keywords: Leishmania spp.; PCR-RFLP; spider monkey